Reliability of the AR-CALUX®In Vitro Method Used to Detect Chemicals with (Anti)Androgen Activity: Results of an International Ring Trial. (24th June 2021) - Milcamps, Anne; Liska, Roman; Langezaal, Ingrid; Casey, Warren; Dent, Matthew; Odum, Jenny
Abstract: The AR-CALUX ® in vitro method is a reporter gene-based transactivation method where endocrine active chemicals with androgenic or anti-androgenic potential can be detected. Its primary purpose is for screening chemicals for further prioritization and providing mechanistic (endocrine mode of action) information, as defined by the Organisation of Economic Cooperation and Development (OECD) conceptual framework for the testing and assessment of endocrine-disrupting chemicals. This article describes the conduct and results of an international ring trial with 3 EU-NETVAL laboratories and the test method developer. It was organized by EURL ECVAM to validate the method by testing 46 chemicals. A very good reproducibility within and between laboratories was concluded (94.7–100% and 100% concordance of classification) with low within and between laboratory variability (less than 2.5% CV on EC50 values). Moreover, the variability is within the range of other validated, mechanistically similar methods. In comparison to the AR-reference list compiled by ICCVAM, an almost 100% concordance of classifications was obtained. This method allows the detection of the agonist and antagonist properties of a chemical. A specificity control test was developed during the validation study and added to the antagonist assay rendering the assay more specific. A comparison is made with the mechanistically similar methods AR-EcoScreen™ and 22Rv1/MMTV GR-KO TA. The AR-CALUX ® method was approved for inclusion in the recently updated OECD test guideline TG458 which incorporates all 3 methods.